PRINSIP DAN STRATEGI PENERAPAN Ã¢â‚¬Å“PUBLIC PRIVATE PARTNERSHIPÃ¢â‚¬Â DALAM PENYEDIAAN INFRASTRUKTUR TRANSPORTASI - utama, dwinanta (Jurnal Sains dan Teknologi Indonesia, 2010)
Public Private Partnership (PPP), recently is becoming popular issue among stakeholders in infrastructure development in Indonesia. In other countries, infrastructure facilities such as Toll Road, Water Supply Network, Electricity Power, Harbour, Airport, Health Services, and Education have already been using PPP scheme. PPP is needed due to the limitation of government budget, infrastructure life time based on the quantity and the quality, and also the private sector skill/technology capability. In term of infrastructure quality competitiveness, based on the survey resulted in the World Competitiveness Report 2008-2009, showed that Indonesia is on the 96th rank among 134 countires surveyed. It can be argued that Indonesian infrastructure quality is still low in comparison to the other South East Asian Countries, even from its neighborhood countries. Government budget for infrastructure investment including transportation in 2010-2014 is very limited namely around 32% including from bilateral and multilateral loan. Therefore the 62% government budget remains must be fulfilled by another scheme such as Public Private Partnership.